2022
DOI: 10.1155/2022/2693776
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Clinical Significance and Correlation Decomposition of Cord Blood NO, Activin A Levels, and MCA/UA with Fetal Distress

Abstract: The clinical significance and correlation of cord blood NO, activin A levels, and middle cerebral artery (MCA)/umbilical artery (UA) with fetal distress are explored. 120 puerperae who delivered in the obstetrics department of our hospital from January 2021 to January 2022 are selected as the examination subjects. According to the diagnostic criteria of fetal distress, they are divided into 70 cases of fetal distress and 50 cases of normal delivery. The parameters of umbilical cord blood NO, activin A, UA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%